Level numbers of a bounded linear operator between normed linear spaces and singular value decomposition revisited. Issue 19 (16th December 2022) - Sain, Debmalya; Roy, Saikat; Tanaka, Ryotaro
ABSTRACT: We introduce the notion of level numbers of a bounded linear operator between normed linear spaces, as a generalization of the singular values of an operator between inner product spaces. We study the geometric and the analytic properties of the level numbers, in connection with Birkhoff–James orthogonality and norm optimization problems. We also illustrate the similarities and the differences between the level numbers and the singular values of an operator. As an application of the present study, we obtain a new and elementary approach to the singular value decomposition of matrices.